Evaluasi Program Art Therapy Bagi Pasien Dual Diagnosis (NAPZA-Skizofrenia) di Rumah Sakit Ketergantungan Obat (RSKO) Jakarta - Ulfah, Nurbani (Social Welfare Study Program, 2015)
The main problem drug users with psychiatric disorders is the difficulty of communicating the reason they use drugs and express their feelings on the condition of the Counselor or Social Worker (Therapist). The existence of the program of art therapy for patients with drug with psychiatric disorders (dual diagnosis) is part of psychotherapy as an adjunct therapy in the form of art to channel emotions, express their feelings when communicate verbally is difficult, and to express themselves freely in order to improve their condition in the direction better in recovering. In an effort to redress for victims of drug abuse, especially for people with dual diagnosis due to drug addiction, the Drug Dependency Hospital (RSKO) is a reference center for rehabilitation using the Therapeutic Community (TC) based hospitals that have programs therapies to restore health and capabilities in the field of art, one through the art therapy program.Keywords: Evaluasi Program, Art Therapy, Dual Diagnosis (NAPZA-Skizofrenia), dan Pekerja Sosial Medis/Klinis.